Effects of microstructure and crystallography on crack path and intrinsic resistance to shear-mode fatigue crack growth - J. Pokluda; T. Vojtek; A. Hohenwarter; R. Pippan (Fracture and Structural Integrity)
The paper focuses on the effective resistance and the near-threshold growth mechanisms in the ferritic-pearlitic and the pure pearlitic steel. The influence of microstructure on the shear-mode fatigue crack growth is divided here into two factors: the crystal lattice type and the presence of different phases. Experiments were done on ferritic-pearlitic steel and pearlitic steel using three different specimens, for which the effective mode II and mode III threshold values were measured and fracture surfaces were reconstructed in three dimensions using stereophotogrammetry in scanning electron microscope. The ferritic-pearlitic and pearlitic steels showed a much different behaviour of modes II and III cracks than that of the ARMCO iron. Both the deflection angle and the mode II threshold were much higher and comparable to the austenitic steel. Mechanism of shear-mode crack behaviour in the ARMCO iron, titanium and nickel were described by the model of emission of dislocations from the crack tip under a dominant mode II loading. In other tested materials the cracks propagated under a dominance of the local mode I. In the ferritic-pearlitic and pearlitic steels, the reason for such behaviour was the presence of the secondary-phase particles (cementite lamellas), unlike in the previously austenitic steel, where the fcc structure and the low stacking fault energy were the main factors. A criterion for mode I deflection from the mode II crack-tip loading, which uses values of the effective mode I and mode II thresholds, was in agreement with fractographical observations.